2016
DOI: 10.1111/sltb.12312
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Identifying the Thought Markers of Suicidal Subjects: A Prospective Multicenter Trial

Abstract: Death by suicide demonstrates profound personal suffering and societal failure. While basic sciences provide the opportunity to understand biological markers related to suicide, computer science provides opportunities to understand suicide thought markers. In this novel prospective, multimodal, multicenter, mixed demographic study, we used machine learning to measure and fuse two classes of suicidal thought markers: verbal and nonverbal. Machine learning algorithms were used with the subjects' words and vocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 49 publications
4
121
0
1
Order By: Relevance
“…machine learning), as some researchers have already begun to do (e.g. Kessler et al., ; Pestian et al., ; Walsh, Ribeiro, & Franklin, ). Machine learning may be particularly helpful with meaningfully integrating the many small to modest effects from risk factors and correlates observed in the field (Franklin et al., ).…”
Section: Treatment Of Suicidal Behaviormentioning
confidence: 99%
“…machine learning), as some researchers have already begun to do (e.g. Kessler et al., ; Pestian et al., ; Walsh, Ribeiro, & Franklin, ). Machine learning may be particularly helpful with meaningfully integrating the many small to modest effects from risk factors and correlates observed in the field (Franklin et al., ).…”
Section: Treatment Of Suicidal Behaviormentioning
confidence: 99%
“…Machine learning methodologies are increasingly used in psychiatric research as they facilitate individual-level prediction of unseen observations, which makes them suitable for the development of clinically useful digital tools [46]. Recent evidence has demonstrated the use of these algorithms to utilize clinical and demographic variables to predict suicide attempters among a group of mood disorder patients with accuracy comparable with most breast cancer prediction algorithms [47,48], whereas another study demonstrated the utility of such algorithms to differentiate between suicidal and nonsuicidal patients [49]. Employing these approaches could improve the personalization of care beyond simple cut-off scores and include key risk factors specific to a particular individual.…”
Section: Discussionmentioning
confidence: 99%
“…A Support Vector Machine (SVM) model was used for classification . SVMs have been proven useful for classification problems such as these, due to their robustness to overfitting and ability to perform well in high‐dimensional spaces . Linear and radial kernels were all considered in training the classifiers, and the kernel with the best overall performance was chosen.…”
Section: Methodsmentioning
confidence: 99%